2020
DOI: 10.3904/kjim.2018.398
|View full text |Cite
|
Sign up to set email alerts
|

The health-related quality-of-life of chronic obstructive pulmonary disease patients and disease-related indirect burdens

Abstract: Background/Aims: Many chronic obstructive pulmonary disease (COPD) patients have physical limitations. We investigated EuroQol five-dimensions five-level (EQ-5D-5L) of COPD patients to assess quality of life, and assessed indirect burden including time expenditure to visit doctor, home care rate, and caregiver related burden. Methods: We recruited 355 COPD patients according to severity of airflow limitation that severity was set at 10% mild, 40% moderate, 30% severe, and 20% very severe in two primary and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…We observed that the proportion of healthcare utilization increased across grades of airflow limitation, as observed previously. 28 However, for participants who visited GPs or hospitalizations in 12 months, the number of GP visits and hospitalizations was not significantly different across the four groups. These results may be attributed to the small number of participants in the GOLD 2 and GOLD 3 or 4 group.…”
Section: Discussionmentioning
confidence: 84%
“…We observed that the proportion of healthcare utilization increased across grades of airflow limitation, as observed previously. 28 However, for participants who visited GPs or hospitalizations in 12 months, the number of GP visits and hospitalizations was not significantly different across the four groups. These results may be attributed to the small number of participants in the GOLD 2 and GOLD 3 or 4 group.…”
Section: Discussionmentioning
confidence: 84%
“…Each dimension has a five-level response corresponding to no problem, slight problems, moderate problems, severe problems, and extreme problems. 24 …”
Section: Methodsmentioning
confidence: 99%
“…A major component of healthcare expenditure is the cost of medication, diagnostics, treatments and hospitalisation. There is also a significant social burden in productivity loss, informal care and loss of Quality-Adjusted Life Years (QALYs) [2][3][4].…”
Section: Introductionmentioning
confidence: 99%